Estoppel In The Law Of Banking And Negotiable Instruments - Sahamid, Badariah (Journal of Malaysian and Comparative Law, 1999)
The area covered by the subject of ’estoppel in the law of banking and negotiable instruments’ is a wide and diverse one. In this pper the discussion will be confied to two areas: (i) forgery of drawer’s signature; and (ii) payment made under a mistake of fact.